Pengaruh Debt To Equity Ratio (Der) Dan Earning Per Share (Eps) Terhadap Harga Saham Pada PT Sentul City Tbk Periode 2008 - 2022 - Mayang Sari Agustin; Fikron Al-Choir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to determine the effect of Debt to Equity Ratio dan Earning Per Share on stock prices at PT.Sentul City Tbk either partially or simultaneously. The research method used in this research is descriptive quantitative research and uses statistical analysis. The population used is the financial statements of PT. Sentul City Tbk. The sample used is data from notes to financial statements, balance sheets and income statements of PT. Sentul City Tbk in the period 2008 to 2022. The variables used in this study consisted of the Debt to Equity Ratio and Earning Per Share, variablesas independent variables and stock price variables as the dependent variable. This research analysis used the SPSS (Statistical Package For Social Science) software program version 25.0. The research results obtained show that the results of the Debt To Equity Ratio (DER) research have no effect on stock prices. Based on the results of the t test (Partial Test), the calculated t value < t table 0.05, namely (-0.584 < 2.17881) is not significant (0.574 > 0.05). Earning Per Share (EPS) has a significant effect on share prices. The t test (Partial Test) shows that t count > t table is significant < 0.05, namely (2.349 > 2.17881) and significant (0.043 < 0.05). Debt To Equity Ratio (DER) and Earning Per Share (EPS) have no effect on share prices based on the F test (Simultaneous Test) which shows that the calculated F value > F table is not significant < 0.05, namely (2.758 < 3.89) no significant (0.116 > 0.05), this shows that there is no significant influence simultaneously between Debt To Equity Ratio (DER) and Earning Per Share (EPS) on share prices. Keywords: Debt to Equity Ratio (DER), Earning Per Share (EPS), Share Price.